PERBEDAAN KECERDASAN EMOSIONAL PERAWAT DI RS SWASTA BERDASARKAN PENGUKURAN EMOTIONAL QUOTIENT BARON-ON DI DAERAH SULAWESI SELATAN - Fr Blasius Perang (Jurnal Keperawatan Florence Nightingale, 2018)
This study aims to determine the level of emotional intelligence (EQ) of nurses in ??private hospital in South Sulawesi. One hundred twenty-three respondents / nurse who worked in the VIP room, emergency room and treatment room are involved in this study were scattered in hospitals, hospitals in South Sulawesi. The specific goal of this research close looks at the emotional Intelligence of nurses in serving the patients. For this purpose, this study uses the raw instrument validity and its reliability has tested. The instrument is the Bar-On Emotional Quotient Inventory: Short Form (Baron EQ-i: S). the instrument consists of 51 items with the components: intrapersonal; interpersonal; Stress Management; adaptation; and general mood. This research is a quantitative description-correlational statistical measurement, frequency and percentage distribution, mean, standard deviation, and Kruskal Wallis. The level or degree of emotional intelligence respondents in the study is significantly high. The lowest level is Baron-On is 70, but indicated by the respondents is very remarkable. This study shows that there are no differences in intelligence emotional of nurses when grouped by gender, level of education and years of service. No significant difference in emotional intelligence of nurse when grouped by area of ??work, except for nurses who work in the VIP room and Nursing room. The results of this study will be used as reference material for hospitals to develop their service quality by improving emotional intelligence (EQ) of nurse with programs that offered by researcher.